International trade and firm innovation: patterns and evidence from the Chinese Employer-Employee Survey data. Issue 1 (2nd January 2017) - Tian, Wei; Yu, Miaojie; Zhang, Rui
ABSTRACT: How international trade fosters firm innovation is crucial in understanding how economic integration boosts productivity growth. This study uses the Chinese Employer-Employee Survey data set, which contains detailed, firm-level information on exports, imports, and innovation. The study documents several stylized facts characterizing the interaction between international trade and innovation among Chinese firms. The main findings are that exporters and importers are exceptional in production and innovation; exporters are more inclined to import material and machinery inputs; domestic and private firms do not seem to be more innovative than their counterparts. Abbreviations : CEES: Chinese Employer-Employee Survey; FIE: Foreign investment enterprise; NBS: National Bureau of Statistics of China; SOE: State-owned enterprise